2021
DOI: 10.3390/jcm10102067
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem-Resistant Klebsiella pneumoniae Infections in ICU COVID-19 Patients—A Scoping Review

Abstract: Introduction: The spread of multidrug-resistant pathogens is a serious problem and challenge for the whole medical community. Carbapenem-resistant Klebsiella Pneumoniae (CRKP) infections in immunocompromised patients have a severe course and may be fatal. Increasingly, these bacteria are exhibiting resistance to carbapenem antibiotics, which have been used as so-called drugs of last resort. The emergence of the new coronavirus and the pandemic that it has caused require changes to protect against the spread of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 49 publications
8
38
0
Order By: Relevance
“…Invasive infections due to multidrug resistant KPC and/or OXA-48 carbapenemase-producing K. pneumoniae have been reported by Dumitru et al [ 58 ] in nine patients hospitalized in an intensive care unit (ICU) with severe COVID-19. Another review study by Medrzycka-Dabrowska et al [ 59 ] reported COVID-19 patients with carbapenem-resistant K. pneumoniae isolates from six countries—Italy, China, Egypt, United States, Spain and Peru—at a prevalence ranging from 0.35% to 53%.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive infections due to multidrug resistant KPC and/or OXA-48 carbapenemase-producing K. pneumoniae have been reported by Dumitru et al [ 58 ] in nine patients hospitalized in an intensive care unit (ICU) with severe COVID-19. Another review study by Medrzycka-Dabrowska et al [ 59 ] reported COVID-19 patients with carbapenem-resistant K. pneumoniae isolates from six countries—Italy, China, Egypt, United States, Spain and Peru—at a prevalence ranging from 0.35% to 53%.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the most frequently isolated resistance gene was KPC, followed by OXA-48 and NDM, being pneumonia and BSI the main source of infection. In contrast, urinary tract, intraabdominal, and skin and soft tissue infections were very rare, probably because the main drivers of dissemination of CR-Kp were identified to be the use of mechanical ventilation and central catheters [45].…”
Section: Carbapenem-resistant Enterobacteriaceaementioning
confidence: 99%
“…In order to intensify the conflict, clinical evidence suggest that inadequate broad-spectrum empiric antibiotic use could be associated with higher mortality, especially in case of sepsis [ 15 ]. Such differing assumptions will eventually result in an unprecedented emergence of AMR and compromise the global efforts to combat AMR [ 16 , 17 , 18 , 19 , 20 , 21 ]. Hence, the World Health Organization (WHO) raised concerns regarding the irrational consumption of antibiotics during the COVID-19 pandemic and strictly prohibited the antibiotic prophylaxis or treatment of the patients with mild or moderate COVID-19 unless indicated [ 16 ].…”
Section: Introductionmentioning
confidence: 99%